Transactions Involving Electric Vehicles for Green Technology (International Journal of Innovative Research in Engineering & Management, 2023)
This study focuses on using consumer  motivation to encourage the adoption of cleaner  technologies. Consumers are varied since they may be  driven by internal or external reasons. Though information  provision methods may be helpful in encouraging some  consumers to purchase electric vehicles. Also, financial  incentive schemes such as discounts or penalties may be  more persuasive to extrinsically driven customers. This  article offers a sophisticated theory of environmental  innovation adoption in which information-provision  methods are complemented with economic incentives. The  different studies have been done to find out the policies for  encouraging customers to reduce the harmful impacts of  transportation system on environment. The projection of  electric cars sales by 2030 is examined. Finally, the  different reasons fueling development of electric cars are  explored in depth. The results of this study would be of  particular relevance to legislators who seek to push  consumers toward greener technologies.
Keywords: Consumers; Environment; Electric Car; OEMs; Vehicles